2021
DOI: 10.3390/su132313142
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Power Outage and Preparedness of the Population of a Region in the Czech Republic—A Case Study

Abstract: The power outages that have occurred in recent years around the world point to widespread problems with consequences for the lives and health of the population, but also material damage. This is a case study that focuses on the evaluation of the preparedness of the population of a selected region in the Czech Republic for a long-term power outage. This article deals with a case study that focuses on the evaluation of the preparedness of the population of the Karlovy Vary region in the field of emergency surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Nevertheless, 88.2% of the participants specified having a backup power system mainly comprising solar panels and electric generators. These findings compare with the results of a previous study by Kavan et al. (2021) on the long-term outages and preparedness of a small community of Karlovy Vary in the Czech Republic.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Nevertheless, 88.2% of the participants specified having a backup power system mainly comprising solar panels and electric generators. These findings compare with the results of a previous study by Kavan et al. (2021) on the long-term outages and preparedness of a small community of Karlovy Vary in the Czech Republic.…”
Section: Resultssupporting
confidence: 83%
“…Nevertheless, 88.2% of the participants specified having a backup power system mainly comprising solar panels and electric generators. These findings compare with the results of a previous study by Kavan et al (2021) on the long-term outages and preparedness of a small community of Karlovy Vary in the Czech Republic. In this study, the authors found that 90.5% of the participants stated that they had a backup power supply to cope with long-term outages and 70.7% relied on a battery-operated radio or car radio for emergency transmission of information after the failure of the backup warning network (regular session at a certain CRR 5,1 time).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Electrical energy can easily be converted into kinetic energy, heat energy, light energy and transmitted over long distances. Modern human society is increasingly dependent on electricity, and any major outage can lead to damage that can have an impact on the very functioning of the state (Karda and Kavan, 2023;Kavan et al, 2021). In view of this, there is an increasing use of renewable sources to produce electricity.…”
Section: Introductionmentioning
confidence: 99%